The glutamine antagonist prodrug JHU-083 slows malignant glioma growth and disrupts mTOR signaling. Issue 1 (29th October 2020) - Yamashita, Alex Shimura; da Costa Rosa, Marina; Stumpo, Vittorio; Rais, Rana; Slusher, Barbara S; Riggins, Gregory J
Abstract: Background: Metabolic reprogramming is a common feature in cancer, and it is critical to facilitate cancer cell growth. Isocitrate Dehydrogenase 1/2 (IDH1 and IDH2) mutations ( IDH mut) are the most common genetic alteration in glioma grade II and III and secondary glioblastoma and these mutations increase reliance on glutamine metabolism, suggesting a potential vulnerability. In this study, we tested the hypothesis that the brain penetrant glutamine antagonist prodrug JHU-083 reduces glioma cell growth. Material and Methods: We performed cell growth, cell cycle, and protein expression in glutamine deprived or Glutaminase ( GLS ) gene silenced glioma cells. We tested the effect of JHU-083 on cell proliferation, metabolism, and mTOR signaling in cancer cell lines. An orthotopic IDH1R132H glioma model was used to test the efficacy of JHU-083 in vivo. Results: Glutamine deprivation and GLS gene silencing reduced glioma cell proliferation in vitro in glioma cells. JHU-083 reduced glioma cell growth in vitro, modulated cell metabolism, and disrupted mTOR signaling and downregulated Cyclin D1 protein expression, through a mechanism independent of TSC2 modulation and glutaminolysis. IDH1R132H isogenic cells preferentially reduced cell growth and mTOR signaling downregulation. In addition, guanine supplementation partially rescued IDH mut glioma cell growth, mTOR signaling, and Cyclin D1 protein expression in vitro. Finally, JHU-083 extended survival in an intracranial IDH1 mut glioma model and reduced intracranial pS6 protein expression. Conclusion: Targeting glutamine metabolism with JHU-083 showed efficacy in preclinical models of IDH mut glioma and measurably decreased mTOR signaling.